ATTITUDE TOWARDS E-LEARNING: THE CASE OF MAURITIAN STUDENTS IN PUBLIC TEIS - Dookhan, Kiran (PEOPLE: International Journal of Social Sciences, 2018)
Universities in Mauritius are looking forward to introduce e-learning systems to satisfy the needs of the growing number of students. Today, it is relatively common for our students to use modern technologies in their day-to-day activities and hence it has resulted into discussing whether there is a need to incorporate these modern technologies in our learning process. This paper tries to bridge the gap by investigating students’ attitudes and patterns of use of a typical e-learning system. The study focuses on the Mauritian university students as the consumer in the e-learning process. A survey was conducted using structured questionnaire to target university students from public HEIs in Mauritius. Out of a sample of 200 respondents only 156 questionnaires were received back where only 150 were found reliable for testing. Data collected was statistically examined using SPSS and the research hypotheses were tested using regression analysis. The results reveal that students are adopting technologies in their studies and wish to use it in a more progressive way.